2004
DOI: 10.1177/0013916504264948
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for and Satisfaction with Migration

Abstract: Background A transformation of healthcare is underway, from a sellers' market to a consumers' market, where the satisfaction of the patient's needs is part of the definition of quality. Patient satisfaction surveys are widely used to judge service quality, but clinicians are sceptical about them because they are too often poorly designed measures that do not lead to improvements in the quality of care.Aim To explore the use of patient satisfaction survey data in identifying problems with the provision of inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In recent years, high residential mobility within and across nations has gradually become an inevitable part in the contemporary world (Baldassare et al, 1979; Hilton and van Minnen, 2002; Ruback et al, 2004; Oishi et al, 2009). Researchers have been trying to uncover the effect of residential mobility on people’s lives across multiple domains, including attachment to community (Sampson, 1988), prosocial behaviors (Oishi et al, 2007b; Lun et al, 2012; Li et al, 2019, Li et al, unpublished), social relationships (e.g., Oishi et al, 2013; Li, 2017), and self-identity (Oishi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high residential mobility within and across nations has gradually become an inevitable part in the contemporary world (Baldassare et al, 1979; Hilton and van Minnen, 2002; Ruback et al, 2004; Oishi et al, 2009). Researchers have been trying to uncover the effect of residential mobility on people’s lives across multiple domains, including attachment to community (Sampson, 1988), prosocial behaviors (Oishi et al, 2007b; Lun et al, 2012; Li et al, 2019, Li et al, unpublished), social relationships (e.g., Oishi et al, 2013; Li, 2017), and self-identity (Oishi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Organisation for Migration (2009), 200 million people, over 3 per cent of world's population, live in a country other than the one in which they were born. Migration can be involuntary in response to war and natural disasters, but is most often voluntary (Ruback et al, 2004), resulting largely from a desire for economic improvement. Migrants are therefore increasingly concentrated in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Community facilities and resources may determine migrants’ satisfaction, with migrants who have access to such facilities more likely to be satisfied than those who do not have such access 21. These studies have shown that dissatisfaction with migration or poor quality of life diminishes the length of stay of migrants in host communities.…”
Section: Introductionmentioning
confidence: 99%